Effect of Grey and White Portland Cement Fillers on Flexural and Shear Strength of GFRP Composite Material - D. Harsha Vardhan; D. Sai Chaithanya Kishore; Y. Santhosh Kumar Reddy; K. Manohar Reddy; Gujjala Raghavendra; Ramesh Rudrapati (Advances in Materials Science and Engineering)
The mechanical behaviour of glass fiber reinforced polymer (GFRP) composite depends on the type of matrix, filler, and fiber architecture. In order to develop high-strength polymer matrix composites, the composites containing 5%, 10%, and 15% each of Portland grey and white cement filler are prepared by uniformly mixing the epoxy and filler materials, followed by casting by hand layup technique. The flexural and shear test is performed in accordance with ASTM 790 and ASTM D5379, respectively. It has been found that the values of shear strength, flexural strength, and modulus of elasticity vary with the increasing amount of cement component in the polymer. In addition, for a given percentage of the components of the cementitious filler, the values of the mechanical strength of the composites that contain white cement are higher than those of the composites that contain grey cement filler. Damage to composites has been found to involve fiber breakage and delamination primarily.